THU0420 Apremilast, An Oral Phosphodiesterase 4 Inhibitor, Is Associated with Long-Term (52-Week) Improvements in BASDAI in Patients with Psoriatic Arthritis: Pooled Results from 3 Phase III, Randomized, Controlled Trials. (15th July 2016) - Mease, P.; Marzo-Ortega, H.; Poder, A.; Van den Bosch, F.; Wollenhaupt, J.; Lespessailles, E.; McIlraith, M.; Teng, L.; Hall, S.
Abstract : Background: In the PALACE psoriatic arthritis (PsA) trials, the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score was obtained as an exploratory measure in a subset of patients (pts) considered by investigators to have axial involvement, although PsA spondylitis was not confirmed by more objective measures such as MRI. Objectives: Assess the impact of apremilast 30 mg BID (APR) on BASDAI over 52 wks using PALACE 1 (NCT01172938 ), 2 (NCT01212757 ), and 3 (NCT01212770 ) pooled data of pts with active PsA despite prior conventional DMARDs and/or biologics. Methods: APR was evaluated in a subset of pts with baseline (BL) BASDAI ≥4 ("subset") over 16, 24, and 52 wks. Results: BL BASDAI ≥4 was reported in 454/1493 (30%) pts. Mean PsA duration was similar between the subset and the rest of the PALACE 1–3 population (BL BASDAI <4: n=1039). Slightly higher percentages of the subset had a history of palmoplantar, nail, scalp, or plaque psoriasis; mean BL psoriasis BSA and % with BSA ≥3% were slightly increased. The subset had higher mean BL values for CRP (1.12 vs 0.93), pain VAS (63.6 vs 53.8), pt's global disease assessment (62.2 vs 53.5), and physician's global disease assessment (PhGA) (59.0 vs 53.0) and markedly worse mean HAQ-DI (1.41 vs 1.08), SF-36v2 PF (30.6 vs 35.8), and FACIT-F (25.7 vs 31.8); TJC was higher (25.1 vs 19.1) and SJC (12.4 vs 10.9) was less differentiated. DAS-28 scores were comparable. Despite disease activity differences, BL concomitant oral DMARDs were similar in both groups: 1 in 61.0% and 2 in 5.5% (subset) vs 1 in 57.8% and 2 in 6.4% (rest of PALACE 1–3 population); MTX was the most common DMARD. In the subset, 73.6% had only been treated with oral DMARDs pre-study and 44.9% with only 1 DMARD; 25.1% had prior biologic use and 9% prior biologic failure, slightly higher percentages vs the other group. Small increases in BL NSAID and analgesic use were noted in the subset. Mean BL BASDAI scores in the subset were 6.6 in APR and 6.4 in placebo (PBO)pts. APR resulted in a greater mean decrease in BASDAI score vs PBO at Wk 16 (−1.53 vs −0.91; P =0.0173) and Wk 24 (−1.64 vs −0.74; P =0.0002); other disease measures significantly improved, including marked HAQ-DI, PhGA, and fatigue improvements (Table ). Long-term improvement was seen across measures, with mean Wk 52 BASDAI reduction of −2.18 (Table ) and mean HAQ-DI improvement of −0.464. Conclusions: In this post-hoc analysis, pts reporting BASDAI ≥4 appear to have added disease burden, with greater disability, pain, fatigue, and global disease ratings; this may not be captured by some disease activity measures, and effective treatment strategies may not have been available. APR resulted in long-term improvements in BASDAI scores and other measures. Further evaluation objectively assessing presence of inflammatory spine disease in PsA and its response to APR is warranted. Disclosure of Interest: P. Mease Grant/research support from: AbbVie Amgen, BiodenIdec, Bristol-Myers Squibb, Celgene, Genentech, Janssen, GlaxoSmithKline, Lilly, Merck, Novartix, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, BiogenIdec, Bristol-Myers Squibb, Genentech, Janssen GlaxoSmithKline, Lilly, Pfizer, UCB, H. Marzo-Ortega: None declared, A. Poder: None declared, F. Van den Bosch Grant/research support from: AbbVie, Celgene Corporation, Janssen, Merck, Pfizer Inc, UCB, J. Wollenhaupt Consultant for: Abbott Laboratories, Bristol-Myers Squibb, MSD, Pfizer, and UCB, E. Lespessailles Grant/research support from: Novartis, Lilly, Servier, Amgen; Speaker's Bureau: Novartis and Lilly, M. McIlraith Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, S. Hall Grant/research support from: Amgen, AstraZeneca, Boehringer Ingelheim, Centocor, GlaxoSmithKline, MSD, Pfizer, Sanofi Aventis, Sanofi Pasteur, Schering-Plough, Serono, and Wyeth, Speakers bureau: Boehringer Ingelheim, GlaxoSmithKline, MSD, Pfizer, Roche, Sanofi Aventis, Schering-Plough, and Wyeth